Pengaruh Kompetensi, Motivasi dan Lingkungan Kerja terhadap Kinerja Guru Yayasan Perguruan Islam Raudhatul Ulum Sakatiga - Winata, Evin; Seri, Herman; Choiriyah, choiriya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research's background was the declining performance of teachers at the Raudhatul Ulum Sakatiga Islamic College Foundation from 2019 to 2022. The aims of this research were (1) to see the effect of competence, motivation, and work environment on the teacher's performance of the Raudhatul Ulum Sakatiga Islamic College Foundation (2) to see the effect of competence on the teacher's performance of the Raudhatul Ulum Sakatiga Islamic College Foundation (3) to see the effect of motivation on the teacher's performance of the Raudhatul Ulum Sakatiga Islamic College Foundation (4) to see the effect of the work environment on the teacher's performance of the Raudhatul Ulum Sakatiga Islamic College Foundation. This research was a causality associative research using a quantitative approach. The population used in this research were MTs, MA, SMPIT, and SMAIT Raudhatul Ulum teachers who had the status of Foundation Permanent Teachers (GTY) at the Raudhatul Ulum Sakatiga Islamic College Foundation, totaling 122 people. The 94 sample was taken using the Slovin formula in the degree of error; the maximum error rate was 5% (0.05). The analytical model used was multiple linear regression analysis with a confidence level of 95% and a significance level of 5% (0.05). The results of this research indicate that (1) simultaneously, there was an effect of competence, motivation, and work environment on the teacher's performance of the Raudhatul Ulum Sakatiga Islamic College Foundation, (2) there was an effect of work competence on the teacher's performance of Raudhatul Ulum Sakatiga Islamic College Foundation (3) partially there was not the effect of motivation on the teachers' performance of the Raudhatul Ulum Sakatiga Islamic College Foundation (4) partially there was not the effect of the work environment on the teachers performance of the Raudhatul Ulum Sakatiga Islamic College Foundation